KARAKTERISTIK LEMPUNG PARIT MALINTANG SEBAGAI KEKAYAAN LOKAL UNTUK BAHAN BAKU KRIYA KERAMIK - Taufik Akbar; Hendratno Hendratno (Institut Seni Indonesia Padangpanjang, 2022)
The paper talked about the character of clay in Parit Malintang, Padang Pariaman District, as a raw material of ceramic craft. This research aims to find a new clay for ceramic craft or terracotta in West Sumatera. This research method is action research and implementation with pottery and solid casting techniques and reviewed materials science of ceramic. The result of this research contains; Characteristics of clays of Parit Malintang is terracotta clay (red earthenware clay) entirely plastic, drying shrinkage of 5%, firing shrinkage of 8% (713°C) and can be used as a raw material of ceramic craft mainly terracotta craft.